Avaliação da interação de nutrientes na aplicação de zinco em sementes de arroz - de Souza, Henrique Antunes [UNESP]; Rozane, Danilo Eduardo; Prado, Renato de Mello; Romualdo, Liliane Maria (Universidade Federal de Uberlândia (UFU), 2010)
The efficient fertilizer use contend micronutrient depends, also, of the interactions that occur with some nutrients. The objective was to study the interaction of zinc with the excessively nutrient ones in function of the application of different doses and sources of Zn saw seed in the culture of the rice. The experiment was carried through in conditions of vegetation house, in the FCAV/Unesp. The used experimental delineation was entirely cazualized, with three repetitions. The treatments had been five doses: 0; 1,0; 2,0; 4,0 and 8,0 g of Zn for kg of seed; e two zinc sources; sulphate of zinc (22% of Zn) and zinc oxide (50% of Zn). The experimental unit was a translucent polyethylene tray, filled with 5 washed thick sand, where 50 seeds of rice had been sown (to var. Caiapo). To the 30 days after the sowing, effected the cut of the plants, separating them in aerial part and roots. From the results of the dry substance and text of nutrients of the aerial part and root of the rice, the accumulation of the nutrients in the respective agencies of the plants was calculated. Becoming fullfilled it variance analysis and the when necessary unfoldings. It had effect of the interactions in distinguishing way between root and aerial part of rice, with regard to the doses and sources.

O uso eficiente de fertilizantes contendo micronutrientes depende, também, das interações que ocorrem com alguns nutrientes. O objetivo foi estudar a interação do zinco com os demais nutrientes em função da aplicação de diferentes doses e fontes de Zn via semente na cultura do arroz. O experimento foi realizado em condições de casa de vegetação, na FCAV/Unesp, campus Jaboticabal-SP. O delineamento experimental utilizado foi o inteiramente casualizado, com três repetições. Os tratamentos foram cinco doses: 0; 1,0; 2,0; 4,0 e 8,0 g de Zn por kg de semente; e duas fontes de zinco; sulfato de zinco (22% de Zn) e óxido de zinco (50% de Zn). A unidade experimental foi uma bandeja de polietileno translúcido, preenchida com 5 L de areia grossa lavada, onde foram semeadas 50 sementes de arroz (var. Caiapó). Aos 30 dias após a semeadura, efetuou-se o corte das plantas, separando-as em parte aérea e raízes. A partir dos resultados da matéria seca e teor de nutrientes da parte aérea e raiz do arroz, calculou-se o acúmulo dos nutrientes nos respectivos órgãos das plantas. Realizando-se a análise de variância e os desdobramentos quando necessários. Houve efeito das interações de maneira diferente na raiz quanto na parte aérea do arroz, em relação às fontes, a forma de sulfato promoveu maior interação em relação à outra fonte.
Evaluation of the interaction of nutrients in the zinc application in seeds of the rice
Keywords: Oriza sativa; Nutrients; Accumulation